CRITICAL SUCCESS FACTORS IN ERP INFOR SYSTEM IMPLEMENTATION AT PT. BALRICH LOGISTICS - Aries Susanty; Fernando Fernando (Operations Excellence: Journal of Applied Industrial Engineering, 2015)
Abstract. Enterprise Resource Planning (ERP) systems have become vitalstrategic tools in today‟s competitive business environment. This researchattempts to identify the most ERP Critical Success Factors (CSF) from someliterature which is suitable for PT. Balrich Logistics and to measure impact ofeach factor in order to have a better understanding and a clearer picture of thefactors that are considered to be vital for a successful ERP INFORimplementation at PT. Balrich Logistics. The sample of this research consisted ofthe user who implemented ERP systems. Data collected through a questionnairewhich distribution to 80 people. Research carried out by using Structural EquationModeling (SEM) which was run by AMOS Program. The results of this researchshowed that vendor support is the vital variable for supporting the successfulimplementation of ERP systems, and then followed by other variables sorted byscore from highest to lowest, namely: top management support, education andtraining, suitability of software and hardware with company need, and the last oneis effective project management. Theoretical implications and suggestions for thecompany from this study have been elaborated at the end of this studyKeywords: ERP, Top Management, Project Management, Software andHardware, Education and Training, Vendor, SEM